Enhancing the Appeal: Impact of Economic Value, Market Value, Return Equity, and Total Assets Turnover on Stock Prices - Balqis, Sitti Bahira; Oktavia, Dinda (SAN Scientific, 2024)
This research aims to determine the influence of economic value added, market value added, return on equity, and total asset turnover on stock prices. The population in this study was companies that were included in the LQ45 index, and the companies selected as research samples were 22 companies. The sampling technique uses a purposive sampling technique. Data were analyzed using descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing using the t-test and determination test. The research results show that partial economic value added and total asset turnover do not affect stock prices; market value added has a positive and significant effect on stock prices, while return on equity has a negative and significant effect on stock prices. Managerial implications, emphasizing the significance of enhancing economic value, market value, ROE, and total assets turnover to drive stock price performance. Managers should focus on strategies that improve these metrics and enhance shareholder value and market competitiveness. Understanding the interplay between economic values. Total assets turnover is vital for effective managerial decision-making in the stock market realm. This study delves into the implications of these factors on stock prices for managers navigating the complexities of financial markets